Efektivitas Pembelajaran Daring Menggunakan Whatsapp Group Terhadap Kemampuan Berpikir Kritis Mahasiswa Pada Mata Kuliah Kewarganegaraan - Yatimah, Siti; Sahid, M.; Faisal, Bagus Imam; Yuniarti, Diah Retna; Sunardjo, Sunardjo (Penerbit STKIP PGRI Bangkalan, 2023)
This study aims to determine the effectiveness of online learning using WhatsApp Group on the critical thinking skills of students of Civics Education Department Class of 2020 in the Citizenship course. This type of research is descriptive quantitative. The instruments used in this study were questionnaires, observation sheets, cognitive tests, and competence-based tests. The results of this study are described as follows (1) students’ responses are said to be positive with a score of 2.43. (2) the average result of the student's cognitive test is 68. (3) the average result of the student's critical thinking ability test is 80. (4) Students’ activity is said to be good with a score of 67% (5) the implementation of the RPS is very good with the acquisition a score of 3.41. So it can be summed up that online learning using WhatsApp Groups is effective on the critical thinking skills of the 2020 Civics Education Department students in the Citizenship course. Keywords: effectiveness of online learning, WhatsApp Group, critical thinking.